2021
DOI: 10.1111/spc3.12644
|View full text |Cite
|
Sign up to set email alerts
|

Call to arms: Research directions to substantiate a unified model of attachment and personality pathology

Abstract: Personality pathology and adult attachment are "made of the same stuff" (Meyer & Pilkonis, 2005). They share crucial phenomenological features, etiologies, and genetic bases; however, these shared features have not been appropriately represented in empirical literature as reflective of a common dysfunction. Continuing to conceptualize attachment and personality pathology as separable constructs shackles clinical efforts, particularly with regard to identifying persons and relationships that may be most prone t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 165 publications
(189 reference statements)
0
1
0
4
Order By: Relevance
“…Some have proposed that attachment and PDs exist on the same continua (with PDs characterizing extremity of attachment insecurity; Blatt & Levy, 2003), while others have suggested that early attachment “sets the stage” for interpersonal dysfunction that later becomes PD (Meyer & Pilkonis, 2005). Regardless of their specific mechanism of association, PDs and attachment share phenotypic similarities that are reflected in robust bivariate associations (i.e., up to r = .79; Meyer & Pilkonis, 2005; Smith & South, 2021). Despite this strong evidence of certain PDs with attachment insecurity based on phenotypic similarities (e.g., dependent PD with anxious attachment), however, the precision of PD–attachment associations to one dimension (i.e., avoidance or anxiety) have not been tested.…”
Section: Adult Attachment and Personality Disordermentioning
confidence: 99%
“…Some have proposed that attachment and PDs exist on the same continua (with PDs characterizing extremity of attachment insecurity; Blatt & Levy, 2003), while others have suggested that early attachment “sets the stage” for interpersonal dysfunction that later becomes PD (Meyer & Pilkonis, 2005). Regardless of their specific mechanism of association, PDs and attachment share phenotypic similarities that are reflected in robust bivariate associations (i.e., up to r = .79; Meyer & Pilkonis, 2005; Smith & South, 2021). Despite this strong evidence of certain PDs with attachment insecurity based on phenotypic similarities (e.g., dependent PD with anxious attachment), however, the precision of PD–attachment associations to one dimension (i.e., avoidance or anxiety) have not been tested.…”
Section: Adult Attachment and Personality Disordermentioning
confidence: 99%
“…Jako jeden z predyktorów zaburzeń osobowości wskazywane jest przywiązanie [1][2][3][4][5]. W literaturze przedmiotu można znaleźć wiele modeli przywiązania i metod do mierzenia wyróżnianych w nich zmiennych, ale w badaniach używana jest zwykle jedna metoda, często w różnych raportach inna, w związku z czym wyniki bywają trudno porównywalne.…”
Section: Wprowadzenieunclassified
“…Badanie uwarunkowań zaburzeń osobowości w ujęciu dymensjonalnym oznacza poszukiwanie predyktorów nasilenia patologicznych cech-domen i jest możliwe również w populacji nieklinicznej. Jednym z takich predyktorów jest przywiązanie [1][2][3][4][5].…”
Section: Anankastycznośćunclassified
See 2 more Smart Citations